PHILOSOPHICAL VALIDITY, THEORETICAL, NORMATIVE AND EMPIRICAL PARADIGM OF GENERAL PRINCIPLES OF GOOD GOVERNANCE (AUPB) AS A REVIEW OF PRESIDENTIAL IMPEACHMENT - Nadir, Nadir; Soedarsono, Soedarsono; Hamidi, Jazim; Syafaat, Muchamad Ali (Faculty of Law, Universitas Brawijaya, 2017)
Philosophical validity showed of the Principles of Good Governance (AUPB) as A review to Presidential impeachment, is a principle of AUPB that contains ethical normative values used as the foundation of good governance, clean and respectable, moreover to complement the shortcomings and ambiguities in law. Technically, the application of AUPB by the judges of the Constitutional Court (MK-RI) can be approached through induction and deduction legal reasoning. The method of implementing AUPB by the judges of the Constitutional Court (MK-RI) is accomplished by deductive at first, meaning that the special rules is focused more to the certain field of law, then these are deducted based on its basic rules and deducted again into the rules of substantive, and deducted again into the rules of cases. After that, it starts to applicate the rules of case based on the concrete case by the judge, because of the nature of the judges of the Constitutional Court (MK-RI) is kholifah filardi as the representative of God on earth to uphold the law and justice. While theoretically AUPB is valid, the judge ius curia Novit as a verdict maker to perform legal discovery (rechtsvinding). Empirically AUPB is valid, it can be seen from the cases of impeachment against the President of the United States William Jefferson Clinton, on suspicion of